Elements of advertisement and their impact on buying behaviour: A study of skincare products in Malaysia - Jan, Muhammad Tahir; Haque, A. K. M. Ahasanul; Abdullah, Kalthom; Anis, Zohurul; E-Alam, Faisal (Growing Science, Canada, 2019)
This paper mainly aimed to identify the impact of critical factors of advertisement on consumer buying behaviour for skincare products. Data for this study were collected from 428 people from all around Malaysia using self-administered questionnaires. The acquired data went through an exhaustive process of screening and cleaning to ensure that it was ready for analyses in SPSS software. Various robust tests were conducted to reach the findings. These include, frequency tests, reliability tests, exploratory and confirmatory factor analysis, and also hypotheses testing. Structural equation modelling was used to test for the fitness of the proposed model. The results revealed that two elements of advertisement; namely, usefulness of advertisement and features of advertisement had significant positive impacts on consumer buying behaviour. A unique attempt was also made to search for a suitable nested model, where features of advertisement resulted in a strong positive significant impact on usefulness of advertisement. This research has invaluable implications for policy makers, especially in cosmetic and health industry of Malaysia. It is hoped that the findings of this study can be considered while making marketing plans for a skincare brand.